KLASIFIKASI RAGAM BACAAN ANAK DI SDN KEDOYA UTARA 09 JAKARTA BARAT - Riyanti Lestari; Khusnul Fatonah (STKIP Subang, 2026)
Children's reading books have an important role in the development of children, especially elementary school age. The aim of this research is to explain the classification of the variety of children's reading at SDN Kedoya Utara 09, West Jakarta, which includes a variety of fiction and non-fiction reading as well as the characteristics of quality children's reading books at the school. Classification is carried out based on Dewy Decimal Classification (DDC) guidelines. This study used descriptive qualitative method. This research data is information obtained based on observations, interviews and documentation of various children's reading books at SDN Kedoya Utara 09, West Jakarta. Data analysis refers to the Miles and Huberman approach which includes data reduction, data presentation, and drawing conclusions. The results of the research explain that the classification of children's reading at school consists of fiction and non-fiction books. The only fiction books found were fairy tales and short stories, while non-fiction books included textbooks, enrichment books and motivational books. Between these two types, nonfiction books dominate more than fiction books. The characteristics of quality children's reading books in schools are differentiated based on class level according to the book format, book theme, book content, and language used. It is hoped that the variety of children's reading books can provide some insight into the importance of choosing reading books, especially for elementary school students.